Wille und Erkenntnis: Synthese, Dualismus oder Aporie? Ein konzeptionelles Grundproblem der Philosophie Schopenhauers - Novembre, Alessandro (Voluntas: Revista Internacional de Filosofia, 2022)
The relationship between will and cognition represents one of the most fundamental issues in Schopenhauer’s philosophy. The possibility of aesthetic experience, which involves a deliverance of cognition from the service of the will, and even more so the doctrine of the redemption through cognition – the fact that cognition can become a “tranquillizer” of the will and bring will to abolish itself – seems incompatible with Schopenhauer’s voluntaristic metaphysics (i.e., with the principle of the “primacy of the will”). This paper aims to analyse this controversial part of Schopenhauer’s discourse, especially in its implications for the system’s logical consistency, and tries to provide a theoretical and genetic explanation of the question.